The Effect of Exercise on Cardiovascular Parameters in Postmenopausal Women: A Systematic Review - Eppy Setyowati; Ragil Putri Fitriyana; Tri Sunu Probolaksono; Sulis Setiyanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Menopause is characterized by a decline in estrogen levels that leads to physiological changes increasing cardiovascular risk, including hypertension, dyslipidemia, reduced cardiorespiratory fitness, and vascular dysfunction. Consequently, cardiovascular disease remains a major public health concern among postmenopausal women. This study aimed to systematically review evidence on the effects of exercise on cardiovascular parameters in postmenopausal women and to identify the most effective exercise modalities for cardiovascular health improvement. A literature review was conducted in accordance with PRISMA 2020 guidelines. Electronic searches were performed in PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2020 and 2025. Study selection followed predefined inclusion and exclusion criteria based on the PICOS framework. Methodological quality was assessed using the JBI Critical Appraisal Checklist. Fifteen studies met the eligibility criteria and were included in the synthesis. The findings consistently demonstrated that exercise significantly improves cardiovascular outcomes in postmenopausal women. Moderate-intensity aerobic exercise was most frequently associated with reductions in systolic and diastolic blood pressure and improvements in VO₂max. Resistance training improved body composition and cardiometabolic biomarkers, while combined aerobic–resistance programs provided broader cardiovascular benefits. High-intensity interval training yielded marked improvements in cardiorespiratory fitness but requires appropriate supervision. Mind–body exercises were associated with improved autonomic regulation and reduced inflammation. Exercise is a safe and effective strategy for improving cardiovascular health in postmenopausal women. A combination of aerobic, resistance, and complementary exercise modalities is recommended to optimize cardiovascular outcomes and support evidence-based menopausal health management.